2021
DOI: 10.1016/j.xinn.2021.100147
|View full text |Cite
|
Sign up to set email alerts
|

Associations of particulate matter with dementia and mild cognitive impairment in China: A multicenter cross-sectional study

Abstract: Summary Ambient air pollution has been shown to be associated with the pathogenesis of dementia and mild cognitive impairment (MCI). However, few studies have examined these associations in well-characterized populations with low residential mobility, similar living habits, and a standardized assessment of both air pollution exposure and clinical outcome. This study examined the associations of long-term exposure to particulate matter (PM) air pollution with dementia and MCI, using data from the Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…17 A growing body of epidemiological evidence suggests that particulate air pollution contributes to dementia, including several longitudinal studies conducted in the United States and around the world. 11,[18][19][20][21][22][23][24][25][26][27][28] The majority of these studies found positive associations between PM 2.5 and dementia. A systematic review and meta-analysis also concluded that exposure to PM 2.5 is associated with a 16% higher risk of dementia per 10 mg/m 3 increase in PM 2.5 concentration.…”
Section: Introductionmentioning
confidence: 99%
“…17 A growing body of epidemiological evidence suggests that particulate air pollution contributes to dementia, including several longitudinal studies conducted in the United States and around the world. 11,[18][19][20][21][22][23][24][25][26][27][28] The majority of these studies found positive associations between PM 2.5 and dementia. A systematic review and meta-analysis also concluded that exposure to PM 2.5 is associated with a 16% higher risk of dementia per 10 mg/m 3 increase in PM 2.5 concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Other recent evidence continues to point towards air pollution accelerating cognitive decline among those already at risk for Alzheimer's Disease (AD) [66], and that certain protective factors of cognitive function and decline, including educational level [67], and physical activity [68] could continue to be protective despite the detrimental effects of PM 2.5 [69,70 ▪ ].…”
Section: Epidemiological Associations Between Air Pollutants and Ment...mentioning
confidence: 99%
“…This direction explores the integration of advanced machine learning with a traditional statistics field, namely causal inference. Causal inference 1 , 2 works to analyze the relationship between a cause and its effect, 3 which has a wide range of real-world applications in both academic and industrial domains, such as medicine, 4 , 5 , 6 climate, 7 political science, 8 , 9 , 10 and online advertising evaluation. 11 , 12 , 13 Treatment effect estimation is a fundamental problem in causal inference, often applied in policy evaluation.…”
Section: Introductionmentioning
confidence: 99%